Scientific and Social Aspects of the Design, Construction, Installation, and Operation of a Meteorological Station for the Cabécar Community of Pú Ksogë, Talamanca, Limón, Costa Rica - Amador, Jorge A. (2022)
In mid-2018, a group of researchers from the Geophysical Research Center and the School of Physics of the University of Costa Rica started a project to share knowledge about weather and climate sciences with the cabécar community of Pú Ksogë (9,591 ° N, 82.978 ° W, 114.4 masl), Talamanca, Limón, Costa Rica. The initiative was supported by leaders and educational authorities of that indigenous community at the end of that year. With local labor input and the respective authorization, an automatic meteorological station (Siwá Etka) was installed and left in operation on the grounds of the community school at the beginning of 2019. Details of this project and the first atmospheric data observed in the history of that community are described in this paper. The lack of adequate community control and the lack of interest of the school authorities in the care of the instruments caused problems that did not allow the project to continue, and the station had to be uninstalled in October 2019. The experience had positive phases, but other aspects such as cell phone and internet connectivity, sometimes of very low quality or non-existent at all, also influenced the decision to discontinue the initiative. Contacts made with an association for local development in the region could be an alternative to give continuity to the project.